2013
DOI: 10.1152/ajpregu.00102.2013
|View full text |Cite
|
Sign up to set email alerts
|

Increase in parasympathetic tone by pyridostigmine prevents ventricular dysfunction during the onset of heart failure

Abstract: Lataro RM, Silva CA, Fazan R Jr, Rossi MA, Prado CM, Godinho RO, Salgado HC. Increase in parasympathetic tone by pyridostigmine prevents ventricular dysfunction during the onset of heart failure. Am J Physiol Regul Integr Comp Physiol 305: R908 -R916, 2013. First published August 28, 2013 doi:10.1152/ajpregu.00102.2013.-Heart failure (HF) is characterized by elevated sympathetic activity and reduced parasympathetic control of the heart. Experimental evidence suggests that the increase in parasympathetic funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
78
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 71 publications
12
78
2
1
Order By: Relevance
“…Our group (8,27) and others (9,18) have demonstrated that baroreflex dysfunction, reduction in parasympathetic modulation, and increased sympathetic response identified after MI may be restored with physiological and pharmacological interventions that act on the cholinergic anti-inflammatory pathway.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Our group (8,27) and others (9,18) have demonstrated that baroreflex dysfunction, reduction in parasympathetic modulation, and increased sympathetic response identified after MI may be restored with physiological and pharmacological interventions that act on the cholinergic anti-inflammatory pathway.…”
mentioning
confidence: 92%
“…Administration of PY improves the autonomic profile (8,9,18,27) and decreases left ventricular (LV) dysfunction following MI in some experimental studies (8,9,18). Two to four weeks of PY administration may ameliorate cardiac remodeling induced by MI via multiple mechanisms, including by increasing mediators of angiogenesis (41), by decreasing proinflammatory cytokine production, and via cardiac fibrosis of the surviving myocardium (21).…”
mentioning
confidence: 99%
“…Furthermore, vagus nerve stimulation in animal studies and in patients with heart failure has shown improvement in cardiac function, suggesting that cholinergic-pathway activation may provide therapeutic benefit (5,18,45,53,). Other studies using drugs to augment the parasympathetic nervous system or influence vagal tone, including acetylcholinesterase inhibitors such as donepezil or pyridostigmine, show evidence of improved ventricular remodeling and autonomic function in animal models of heart failure or after myocardial infarction (13,26,32,37,42). Studies of patients treated with these drugs for Alzheimer's dementia have reported reduced adverse cardiac events, including myocardial infarction and death (31).…”
mentioning
confidence: 99%
“…In another animal study by Lataro et al, the use of Pyridostigmine in heart failure models was associated with decrease in myocyte diameter, increase in stroke volume, cardiac output and contractility. 20 At 4 weeks of treatment, Pyridostigmine group had an EF of 25% compared to 15% in the control group. Pyridostigmine group had a higher level of vascular endothelial growth factor expression (suggesting angiogenesis) and a higher collagen density in cardiac myocytes.…”
Section: Pyridostigminementioning
confidence: 92%
“…17 None of the studies involving pro-cholinergic agents in the treatment of heart failure have reached clinical application yet. [18][19][20][21][22] Pyridostigmine is a reversible acetylcholine esterase inhibitor, it augments the effect of the parasympathetic system. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] It is currently used in the treatment of myasthenia gravis.…”
Section: Pyridostigminementioning
confidence: 99%